Stability and Adaptability of Nine Open Pollinated Varieties of UB Maize - Waluyo, Budi; ., Kuswanto (AGRIVITA, Journal of Agricultural Science, 2010)
Open pollinated maize and two check varieties were evaluated in four locations, i.e. Malang, Jombang, Kediri, and Trenggalek regencies for two seasons from March to November 2009. The research objective was to determine stability and adaptability of the open pollinated maize. The experiment was conducted using a randomized complete block design. The treatment had nine lines, i.e. UB4101, UB3101, UB4201, UB7201, UB4202, UB3301, UB4301, UB7301, UB3302 and two check varieties, Bisma and Arjuna. The treatment was repeated three times. Percentage point of variance ratio was applied to determine homogeneity error. Variance analysis of combined experiment was conducted to determine genotype x environment interaction. Yield stability and adaptability were analyzed using Eberhart and Russell linear models. There was genotype x season x location interactions on maize yield. It mean that there were population yield performance changes at different environments. There were four populations have stability point, i.e. UB4101 (5.5 t ha-1), UB3301 (5.7 t ha-1), UB7301 (5.7 t ha-1), and UB3302 (5.4 t ha-1). Population UB4201 (5.1 t ha-1) was adaptable to productive environment, and UB4301 (5.8 t ha-1) was adaptable to marginal ones.Keywords: G × E interaction, stability, adaptation, open pollinated maize variety, UB line